2012
DOI: 10.1182/blood-2011-04-350025
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor Erg regulates expression of histone deacetylase 6 and multiple pathways involved in endothelial cell migration and angiogenesis

Abstract: The endothelial ETS transcription factor Erg plays an important role in homeostasis and angiogenesis by regulating many endothelial functions including survival and junction stability. Here we show that Erg regulates endothelial cell (EC) migration. Transcriptome profiling of Ergdeficient ECs identified ϳ 80 genes involved in cell migration as candidate Erg targets, including many regulators of RhoGTPases. Inhibition of Erg expression in HUVECs resulted in decreased migration in vitro, while Erg overexpression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 39 publications
3
80
0
Order By: Relevance
“…Knockdown of ERG resulted in the downregulation of 202 genes, including CLDN5, RASIP1 and ARHGAP28 in serumstarved cells (Fig. S4A), consistent with previous studies (Birdsey et al, 2012;Yuan et al, 2012), and the upregulation of 68 genes. Gene ontology (GO) analysis revealed that the most frequent functional categories altered following loss of ERG were: response to wounding, inflammation, cell migration, cell motility and cell adhesion (Fig.…”
Section: Erg Regulates a Network Of Constitutive And Vegf-inducible Gsupporting
confidence: 78%
See 1 more Smart Citation
“…Knockdown of ERG resulted in the downregulation of 202 genes, including CLDN5, RASIP1 and ARHGAP28 in serumstarved cells (Fig. S4A), consistent with previous studies (Birdsey et al, 2012;Yuan et al, 2012), and the upregulation of 68 genes. Gene ontology (GO) analysis revealed that the most frequent functional categories altered following loss of ERG were: response to wounding, inflammation, cell migration, cell motility and cell adhesion (Fig.…”
Section: Erg Regulates a Network Of Constitutive And Vegf-inducible Gsupporting
confidence: 78%
“…Crucially, mutation of S215 to alanine, an amino acid refractory to phosphorylation (a so-called 'phospho mutant'), abolishes ERG function in prostate cancer cells (Selvaraj et al, 2015). Although several studies have implicated ERG as a mediator of EC survival, proliferation, motility and vascular integrity (Birdsey et al, 2008(Birdsey et al, , 2012(Birdsey et al, , 2015Liu and Patient, 2008;Yuan et al, 2011), whether ERG acts as a hub, integrating signals downstream of VEGF to control these diverse EC behaviors is not known.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 It is also constitutively expressed in normal endothelial cells and regulates angiogenesis and endothelial apoptosis. [18][19][20] Several studies have shown anti-ERG antibody useful for prostate carcinoma, metastatic and primary, and prostatic intraepithelial neoplasias. [10][11][12]21,22 The detection of ERG is highly correlated with both ERG rearrangement by fluorescence in-situ hybridization and with ERG mRNA overexpression.…”
mentioning
confidence: 99%
“…vWF is a common marker for evaluating angiogenesis in vivo and ex vivo [12], while ERG is a member of the ETS (erythroblast transformation-specific) family of transcription factors which is selectively expressed by endothelial cells, specific haematopoetic cells and pre-cartilage cells. It has been shown that ERG plays an important role in blood vessel homeostasis and angiogenesis by regulating a variety of endothelial cellular functions including survival, junctional stability and migration [26]. Physiologically, airways blood vessel homeostasis likely reflects a balance between the production of endogenous angiogenic activators and inhibitors.…”
Section: Discussionmentioning
confidence: 99%